Jaundice as an index of choledochal lithiasis: A fallacious fact - Müller, Augusto; Chevalier, Nelma; Delgado, Bolívar (Cirugía del Uruguay, 1986)
Discussion of 198 cases of biliar,1-panc:reatic pathology. Among the 51 patients affected by jaundice, a sub-group of 28 cases with uninhabited choledochus are specially studied. The conclusion is drawn there is a significant statistical relationship between the jaundice and choledocholithiasis. Stress is laid on the poor reliability of this sign as an indictor of choledocholithiasis.